Thermal Analysis of Co-Utilization of Empty Fruit Bunch and Silantek Coal Under Inert Atmosphere Using Thermogravimetric Analyzer (TGA) - Hamzah, Nurul Syazmimi; Idris, Siti Shawalliah; Rahman, Norazah Abd; Abu Bakar, Noor Fitrah; Matali, Sharmeela (Frontiers in Energy Research, 2021)
Agricultural residues have been traditionally used as energy resources for many years. In light of current environmental and fossil fuel supplies for energy applications, agricultural residues are regarded as sustainable supplies for energy production. However, the suitability to be renewable fuel and as a co-fuel in coal combustion facilities has to be investigated. A thermal analysis was conducted to investigate the effect of the blending and heating rate of the thermal behavior of Malaysian bituminous coal (Silantek), oil palm biomass (empty fruit bunch), and their blends using thermogravimetric analysis. The investigation was done in an inert atmosphere at the heating rate of 10, 20, and 40°C/min. Characteristics including proximate, ultimate, and calorific analyses were also examined. Six different mass ratios were selected from both samples to study the effect of blending of the two materials. The results showed that thermal degradation of empty fruit bunch (EFB) occurred in three stages while Silantek coal (SC) only involved two regions due to their different fuel properties. The blending of both SC/EFB did not follow their individual samples, which showed non-additive behavior suggesting that there is an interaction between coal and biomass. The outcome of this research provides insight on the behavior of Malaysian bituminous coal and oil palm biomass, which enhances knowledge for the future of energy generation.